Production of selenium nanoparticles occurs through an interconnected pathway of sulphur metabolism and oxidative stress response in Pseudomonas putida KT2440 - Avendaño Vega, Roberto (2023)
The soil bacterium Pseudomonas putida KT2440 has been shown to produce selenium nanoparticles aerobically from selenite; however, the molecular actors involved in this process are unknown. Here, through a combination of genetic and analytical techniques, we report the first insights into selenite metabolism in this bacterium. Our results suggest that the reduction of selenite occurs through an interconnected metabolic network involving central metabolic reactions, sulphur metabolism, and the response to oxidative stress. Genes such as sucA, D2HGDH and PP_3148 revealed that the 2-ketoglutarate and glutamate metabolism is important to convert selenite into selenium. On the other hand, mutations affecting the activity of the sulphite reductase decreased the bacteria's ability to transform selenite. Other genes related to sulphur metabolism (ssuEF, sfnCE, sqrR, sqr and pdo2) and stress response (gqr, lsfA, ahpCF and sadI) were also identified as involved in selenite transformation. Interestingly, suppression of genes sqrR, sqr and pdo2 resulted in the production of selenium nanoparticles at a higher rate than the wild-type strain, which is of biotechnological interest. The data provided in this study brings us closer to understanding the metabolism of selenium in bacteria and offers new targets for the development of biotechnological tools for the production of selenium nanoparticles.